OPTIMALISASI OKUPANSI MELALUI REVPAR: ANALISIS STRATEGI REVENUE MANAGEMENT - Edward Priya Munggaran; Mukhamad Kholil Aswan (LPSDI Bina Patria, 2025)
This study aims to analyze the implementation of revenue management strategies in increasing the revenue of three-star hotels, with a focus on market segmentation, pricing, and the role of Online Travel Agents (OTAs). This topic is important because the competition in the hotel industry is getting tighter, so an adaptive and efficient revenue management strategy is needed. The study used a qualitative approach with a case study method. Informants were selected purposively from three main categories: General Manager, Revenue Manager, and Front Office Manager. Data were collected through in-depth interviews and documentation. The results of the study indicate that dynamic pricing strategies, utilization of OTAs, and bundling promotions can significantly increase Average Daily Rate (ADR), occupancy, and RevPAR. However, challenges such as high commission fees from OTAs and inaccurate demand predictions are still obstacles to implementation. The success of the strategy is greatly influenced by coordination between departments and management's ability to respond quickly to market changes. These findings demonstrate the importance of system integration and cross-functional collaboration in supporting effective revenue management in the hotel industry.